2016
DOI: 10.15243/jdmlm.2016.041.703
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics pattern with the depth as affected by forest conversion to rubber plantation

Abstract: Abstract:This research was an attempt to study the impact of forest conversion to intensive rubber plantation on soil characteristics. We selected three landuses (forest, jungle rubber, and rubber plantation) in Bukit Duabelas and Harapan landscape, Jambi, and each repeated three times. Soil profiles were described and sampled at every 10 cm layer to 200 cm depth. Soil bulk density, pH, exchangeable basic cations content, and CEC were determined. The result showed that in three landuses, bulk density is relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The variability of soil physical properties among slope positions was expected due to differences in the thickness of material deposition from volcanic eruptions; supported by the positive correlation between clay fraction and soil bulk density at depth 10-30 cm and 30-50 cm (r = 0.58 and 0.77, p ≤0.05). Agustina et al (2016) reported that the amount of clay increased along with the increase in soil depth was found in the forest land. In addition, the positive correlation between BD and clay content was also found from the previous research conducted in Croatia forest, the western edge of the Pannonia Basin by Rubinić and Safner (2019), which means that the addition of clay is accompanied by an increase in soil BD.…”
Section: Resultsmentioning
confidence: 97%
“…The variability of soil physical properties among slope positions was expected due to differences in the thickness of material deposition from volcanic eruptions; supported by the positive correlation between clay fraction and soil bulk density at depth 10-30 cm and 30-50 cm (r = 0.58 and 0.77, p ≤0.05). Agustina et al (2016) reported that the amount of clay increased along with the increase in soil depth was found in the forest land. In addition, the positive correlation between BD and clay content was also found from the previous research conducted in Croatia forest, the western edge of the Pannonia Basin by Rubinić and Safner (2019), which means that the addition of clay is accompanied by an increase in soil BD.…”
Section: Resultsmentioning
confidence: 97%
“…soil carbon (Guillaume et al, 2015); soil fertility and soil physical properties in the newly established land use systems (Dechert et al, 2004;Klinge et al, 2004). These also lead to different pedogenesis processes (Agustina et al, 2016); higher leaching sensitivity (Kurniawan et al, 2018); higher runoff and erosion (Dariah et al, 2004;Mohammad and Adam, 2010), in tea plantation (Li et al, 2012), coffee-based agroforestry systems (Widianto et al, 2004), cacao (Dawoe et al, 2014), and oil palm plantation (Sunarti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%